The effects of L-tryptophan and pentoxiphylline on stress ulcer - Bülbüller, Nurullah; Akkuş, M Ali; Ilhan, Y Selim; Baysal, Feridun; Ozercan, Ibrahim; Aygen, Erhan; Kirkil, Cüneyt (My University, 2003)
BACKGROUND: It is well known that stress leads to the formation of gastric mucosal lesions. Free oxygen radicals play an important role in the pathogenesis of inflammation and tissue damage. It was observed that L-tryptophan has a positive effect on gastric mucosal damage in ischemia-reperfusion injury by inhibition of free oxygen radicals. The protective effect of pentoxifylline was shown in gastric mucosal damage induced by ischemia - reperfusion or the application of some topical agents. We performed an experimental study to determine whether intragastric L-tryprophan and intramuscular pentoxifylline protect gastric mucosal damage that is induced by immobility stress. METHODS: Forty rats were immobilized and divided into four groups. No treatment was made in the first group; in group 2,3 and 4, L-tryptophan, pentoxifylline and L-tryptophan + pentoxifylline were administered, respectively. The gastric lesions were assessed macroscopically and microscopically two hours following treatment. RESULTS: In the second and fourth groups, the lesion surface area and average mucosal damage were fewer in comparison to the control group (p<0,03). Moreover, an histopatologically improvement in the surface epithelium was observed in these groups. The average lesion score also reduced significantly (p<0,03) only in the L-tryptophan group. On the other hand, no statistically significant improvement was observed in the pentoxifylline group. CONCLUSION: As a result, it was concluded that L-tryptophan could play a protective role in the gastric mucosal damage associated with stress.
L-triptofan ve pentoksifilinin stres ulseri uzerine etkisi.
Keywords: Administration, Oral; Animals; Cattle; Free Radical Scavengers; Gastric Mucosa; Immobilization; Injections, Intramuscular; Pentoxifylline; Rats; Rats, Wistar; Stomach Ulcer; Stress; Tryptophan; pentoxifylline; scavenger; tryptophan; animal; article; cattle; drug effect; immobilization; intramuscular drug administration; oral drug administration; pathology; rat; stomach mucosa; stomach ulcer; stress; Wistar rat